The Effect of Instructive Program Using the Video on Alluding Skill in Basket-Ball for Secondary Students - djamel, mokrani (Universitas Negeri Semarang, 2018)
The research aimed to know the effect of using the video in instructive lessons to ameliorate the alluding skill level for secondary students (16 – 17) years in Mostaganem – Algeria. The researchers used the practical way by using previous and later exam on a design of 24 students separated on two groups once is practical and other is exactive in scholar season 2014/2015. The exams used presented in exams measure practice in alluding skill in basket-ball (alluding from stability, from jumping and alluding from step). After statistic traitment of the results, the researcher found that; The instructive program by using the video affected in amelioration of alluding skill in basket-ball for secondary students. The practical design dominates on instructive program using the video on exactive design counted on traditional way in alluding skill results in basket-ball.